EFFECT OF LAND TREATMENT MEASURES ON SHAPE OF UNIT HYDROGHAPH IN IB SUB-CATCHMENT OF HIRAKUD RESERVOIR - Sharma, K.N.; Sharma, S.D.; Sahu, A.P. (Journal of Soil and Water Conservation, 2022)
Total 59 number of hydrographs for Sundergarh and Deogaon lb sub-catchments were identified and isolated front daily discharge records. Using computer programmeme, base flow separation was done and ordinates of surface runoff hydrographs war determined, Unit hydrographs were derived by the principle of proportionality. Finally representative unit hydrographs for different months for each sub-period were determined for both the sub-catchments. Base time, recession time and discharge of unit hydrographs were used to interpret the hydrological response of the sub-catchments to soil conservation measures.